A method of abrasive wear is for determination of superficsal energy of crystals - Дворук, В. І. (Problems of Tribology, 2019)
As a result of the energy analysis, the theoretical foundations for the process of abrasive wear of ductile and brittle crystals from the point of view of surface energy have been developed on which a method for its determination has been constructed. Using the method of abrasive wear, a generalized formula for determining the surface energy is obtained, which takes into account the structure of plastic and brittle crystals. It is established that the coefficient of stress concentration of the crystal lattice, caused by the carriers of destruction - microcracks in a brittle crystal, contributes to an effective increase of its surface energy than the coefficient of stress concentration of the crystal lattice caused by the carriers of plastic deformation - dislocations and disclinations in a plastic crystal. It is shown. that the specific surface energy has a minimum value and is constant only for an ideal crystal, while for a real crystal this is a structurally sensitive characteristic that depends on structural, technological and operational factors. An experimental verification of the abrasive wear method for determining the surface energy of plastic and brittle crystals was carried out, the results of which confirmed its adequacy. Thus, there is reason to argue that the application of the abrasive wear method to determine the surface energy of plastic and brittle can be made possible. This method is sufficiently developed theoretically and experimentally. It gives the values ​​of the surface energy of crystals of acceptable accuracy